Biosurfactant production by Arctic and Antarctic bacteria growing on hydrocarbons - Malavenda, Roberta; Rizzo, Carmen; Michaud, Luigi; Gerçe, Berna; Bruni, Vivia; Syldatk, Christoph; Hausmann, Rudolf; Lo Giudice, Angelina (Polar Biology, 2015)
The risk of hydrocarbon contamination in marine polar areas is constantly increasing. Autochthonous bacteria, due to their ability to cope and survive under extreme environmental conditions, can play a fundamental role in the hydrocarbon degradation. The degradation process is often enhanced by the production of biosurfactant molecules. The present study reports for the first time on the isolation of biosurfactant-producing bacteria from Arctic and Antarctic shoreline sediments. A total of 199 psychrotolerant bacterial isolates were obtained from hydrocarbon-amended (with crude or diesel oil) microcosms. A total of 18 isolates were selected for their ability to grow in the presence of crude oil and produce biosurfactants, as it was revealed by the production of good E24 values (≥50 %) and/or reduction in the surface tension (under 30 mN/m). The positive response of the isolates to both tests suggests a possible production of biosurfactants with emulsifying and interfacial activities. Biosurfactant-producing isolates were mainly affiliated to the genera Rhodococcus (14 isolates), followed by Pseudomonas (two isolates), Pseudoalteromonas (one isolate) and Idiomarina (one isolate). Thin-layer chromatography of biosurfactant crude extracts revealed that the majority of the selected isolates were able to produce glycolipidic surfactants. Our results enlarge the knowledge, which is still poor and fragmentary, on biosurfactant producers from polar areas and indicate marine polar sediments as a source of bacteria with potential applications in the remediation of hydrocarbon-contaminated cold environments.